2020
DOI: 10.1186/s40795-020-00365-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk fat-based infant formulae on stool fatty acid soaps and calcium excretion in healthy term infants: two double-blind randomised cross-over trials

Abstract: Background Palmitic acid (PA) is predominantly esterified at the SN-2 position of triacylglycerols in human milk. PA at the SN-2 position is more efficiently absorbed and results in reduced formation of PA soaps, as well as reduced fatty acid (FA) and calcium malabsorption. Bovine milk fat (MF), a natural source of SN-2-palmitate, was used in the fat blend of infant formulae (IF) in the current study to investigate its effect on stool fatty acid soaps, calcium excretion and stool characteristics. Methods Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 26 publications
(70 reference statements)
2
20
0
Order By: Relevance
“…In addition, there are infant formulas, including formulas with bovine cream or anhydrous milk fat and whole goat milk formulas, that contain milk fat blended with vegetable oils to provide total and sn -2 palmitic acid without the use of palm oil or structured triglycerides. 46,77 Manios et al 78 found that infants fed a formula with up to 50% of its lipids as milk fat had lower excretion of palmitate soaps, total fatty acid soaps and calcium compared to infants fed a control vegetable oil-based formula.…”
Section: Composition Of Human Milk and Different Infant Formulasmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are infant formulas, including formulas with bovine cream or anhydrous milk fat and whole goat milk formulas, that contain milk fat blended with vegetable oils to provide total and sn -2 palmitic acid without the use of palm oil or structured triglycerides. 46,77 Manios et al 78 found that infants fed a formula with up to 50% of its lipids as milk fat had lower excretion of palmitate soaps, total fatty acid soaps and calcium compared to infants fed a control vegetable oil-based formula.…”
Section: Composition Of Human Milk and Different Infant Formulasmentioning
confidence: 99%
“…48 In addition, whole goat milk formulas and cow milk-based formula including milk fat mixed with vegetable oils have also been proven to improve stool characteristics (Table 2). 77,78…”
Section: Common Digestive Issues In Early Life and Nutritional Solutionsmentioning
confidence: 99%
“…Parents collected stool samples of ~30 g during the last three days (days 12-14) of the run-in period and each of the two intervention periods following a previously described procedure (5). The frozen samples were shipped in dry ice to Euro ns Laboratories, Madison, Wisconsin, USA, to analyse the fat composition and calcium concentration as described previously (5).…”
Section: Stool Collectionmentioning
confidence: 99%
“…Recently, the similarity index has been developed as a tool to design the optimal composition of fat blends (4). Indeed, an infant formula with a mixed fat blend of selected vegetable oils and bovine milk fat (50%) reduced faecal soap formation and improved stool consistency compared to a standard IF with 100% vegetable fat in a recent clinical study (5). In addition to an effect on stool consistency, faecal soaps might also in uence gut microbiota composition and activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, palmitic acids at the sn‐1 and sn‐3 position are released into the gut and can then bind minerals like calcium to form insoluble soaps, especially calcium palmitate (CP). Such soaps can cause a hard stool, and lower the calcium and fatty acids absorption (Manios et al, 2020; Havlicekova et al, 2015). Changed stool consistency suggests that CP formation might influence the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%